2020
DOI: 10.1016/j.foodchem.2020.126927
|View full text |Cite
|
Sign up to set email alerts
|

Human milk pasteurisation reduces pre-lipolysis but not digestive lipolysis and moderately decreases intestinal lipid uptake in a combination of preterm infant in vitro models

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Given that pasteurization, prior the administration, of mother’s own milk is not recommended [ 59 ], also potential pathogenic microorganisms are normally conveyed to preterm infants fed with fresh HM. Nevertheless, breastfeeding is recommended because the potential benefits of breast milk outweigh the possible negative effects: only few articles reported that neonatal infection was caused by the ingestion of contaminated HM [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that pasteurization, prior the administration, of mother’s own milk is not recommended [ 59 ], also potential pathogenic microorganisms are normally conveyed to preterm infants fed with fresh HM. Nevertheless, breastfeeding is recommended because the potential benefits of breast milk outweigh the possible negative effects: only few articles reported that neonatal infection was caused by the ingestion of contaminated HM [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…We then studied the impact of knocking out MTTP or SAR1B on the expression of different genes involved in lipid metabolism [ 19 ] and oxidative stress management. We explored the expressions of genes involved in fatty acid transport ( FATP4 , FABP2 ), intracellular lipid re-synthesis ( ACAT2 , DGAT1 , DGAT2 , MGAT2 ), lipid droplet ( PLIN2 ) or chylomicron ( APOB ) formation, cholesterol metabolism ( ABCA1 , ABCG8 , NPC1L1 , SCARB1 , PGP ) and oxidative stress management ( CAT , SOD1 ).…”
Section: Discussionmentioning
confidence: 99%
“…All images were collected under light microscopy (Olympus BX63, 60 × 10). Intracellular lipid droplets were quantified as described by Vincent et al [ 19 ] after acquiring 20 images per slide by standard light microscopy. Oil Red O-stained cell images were thresholded for the lipid droplet signal using the freely available imaging software ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, bile salt-stimulated lipase in DHM is known to be destroyed by Holder pasteurisation [ 56 , 57 ]. Reduced lipid hydrolysis might thus be a factor in the reduced overall growth inhibition observed in Holder-pasteurised DHM and in Holder-pasteurised FD-DHM.…”
Section: Discussionmentioning
confidence: 99%